Women in policing around the world: doing gender and policing in a gendered organization - Garcia, Venessa (Advances in police theory and practice series, 2021)
"Women in Policing around the World is a historical, legal, political, and social examination of women in policing. The book opens with a comparison of cultural definitions of gender and how this affects women's work in general and policing specifically. The book then takes the reader through women in policing in the Eastern and Western Hemispheres, featuring several countries within the major regions of the world. Major commonalities and differences are identified in the areas of recruitment, training, deployment, promotion, and violence against women. Among the keys features of this book is a balanced coverage of historical and timely events that led to the current status of women police in their respective countries. The book identifies the commonalities that women police experience throughout the world relying on the most current research. The book also dedicates coverage of policing violence against women in society as well as within the police organization itself. The author includes tables to allow for national comparisons throughout the book, as well as current and historical photos. This book is intended for researchers and students of police culture and women in policing. It does not rely heavily on one country or region, thus allowing for an enlightening international comparison"--